A new scheme to analyze and solving an equality constraint-based fully fuzzy linear programming problem under trapezoidal fuzzy uncertainty - Behera, Diptiranjan (International journal of system assurance engineering and management, 2025)
A fully fuzzy linear programming problem with equality fuzzy constraints has been taken into consideration for the analysis. Here the involved parameters and variables are considered in terms of trapezoidal convex normalized fuzzy sets. In this regard, a new method has been proposed to solve the problem. Accordingly, the problem is first defuzzified into a crisp problem using the concept of the area of a trapezoidal fuzzy number for the objective function and next applying general fuzzy arithmetic rules for the constraints and non-negative restrictions. Solving this crisp linear programming problem one can get the bounds of the core and support of the optimal fuzzy solution. Various numerical example problems have been solved and compared with the existing results for the validation.